Cross-border environmental cooperation in the European Union: an analysis of biosphere reserves as instruments of ecological integration - Róbert Király (Annales Scientia Politica)
The paper focuses on the analysis of cross-border cooperation in the field of environmental policy through a comparative assessment of three biosphere reserves: Mura–Drava–Danube, the Eastern Carpathians, and the Danube Delta. The research is grounded in the concept of multi-level governance and is conducted using qualitative analysis of primary and secondary sources. The aim is to identify key factors influencing the success of joint management, coordination, and stakeholder participation. The findings reveal varying levels of institutionalization and actor involvement across the reserves, as well as their respective contributions to fulfilling the objectives of the European Green Deal.